KEPEMIMPINAN PENDIDIKAN DAN ESSENTIAL TRAITS - Ermi Sola (Universitas Islam Negeri Alauddin Makassar, 2020)
In general, leadership is an activity that motivate others to do something. It is clearly stated that leadership is more than just to ‘motivate’. It deals with some one’s ability to lead, and influence others individually or groups to what the leader wants in order to achieve a desired goal (s). Leadership is important in an organization, include education. Principal’s leadership most likely influences the success or failure of the schools. A principal has a big responsibility toward his school management as a whole, such as educational program teaching and learning, administration, guiding the staff, using and maintaining school’s infrastructures. Besides, the principal has to optimize his role and educational functions, i.e. leader, motivator, educator, supervisor, administrator, innovator, manager. Those responsibilities can be carried out well if the principal has qualities that makes him a great leader as a leader.